The age of sustainable development - Sachs, Jeffrey D. (Columbia University Press, 2015)
"The Age of Sustainable Development is both sobering and inspiring: sobering because it presents in great detail the unprecedented challenges facing mankind; inspiring because it assures us that we can meet those challenges, if only we summon the will to act." - from book cover.